Implementasi Terapi Murottal Al-Quran Pada Ny. A Dengan Nyeri Akut Post Sectio Caesarea di RSUD Indramayu - Amma Nur’aisah; Nengsih Yulianingsih (NAJ Nursing Applied Journal, 2024)
Background: Sectio Caesarea (SC) is a birth process through surgery in the abdominal area which will cause disruption of tissue and nerve continuity, resulting in pain in the post section caesarean incision area. Efforts to reduce pain with pharmacological and non pharmacological techniques, one of the non-pharmacological techniques is distraction techniques. This distraction technique is used to divert attention to pain and reduce pain. One effective distraction technique is murottal therapy. Murottal therapy is a form of nursing care, which teaches patients to provide therapy by listening to verse from the holy Koran. Objective: This case study is to determine the development of pain before and after the implementation of Murottal Quran therapy in Mrs. A with acute pain Post Sectio Caesarea at RSUD Indramayu. Method: This case study is a descriptive method with a case study approach and uses a nursing process approach. Results: There was a decrease in the pain scale in Mrs. A post caesarean section at Indramayu Regional Hospital from the moderate pain scale category to the mild pain scale category. Conclusion: Al-Quran murottal therapy has a positive impact on patients with acute pain post Sectio caesarea.